The Function of Dramatic Persona in the Film “The Menu” (2022) - Munawaroh, Silvi; Heriyati, Nungki (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
This study aims to determine the portrayal of characters in the film The Menu 2022. In examining the characters in the film, The Menu, researcher conducted a characterization analysis which was classified into seven functions of dramatic characters through the theoretical framework of Vladimir Propp. This study is used because narratology theory can focus on the actions of a character who is limited in terms of meaning. Through this classification, researchers can find out the depiction of characters and the limits of their actions. The data collection method is carried out by qualitative methods and narrative analysis by collecting research results in the form of descriptions accompanied by screenshots. This study produced findings in the form of depictions of seven-character functions contained in the film "The Menu". The resulting conclusions, based on the data and analysis conducted in this research, reveal a deeper understanding of the narrative structure character’s function using dramatic persona analysis in the film "The Menu" and identify the roles and functions of the characters in the film. The result of this research, researcher found 7 dramatic persona function in the film. Such as, the villain, the donor, the helper, the dispatcher, princess/prize, the hero, and the false hero. Keywords: The Menu Movie, Vladimir Propp, Dramatic Persona, Narratology